Digital Forensics and Watermarking 10th International Workshop, IWDW 2011, Atlantic City, NY, October 23-26, 2011, Revised Selected Papers - Shi, Yun Qing.; Kim, Hyoung-Joong.; Perez-Gonzalez, Fernando; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the 10th International Workshop on Digital-forensics and Watermarking (IWDW 2011) held in Atlantic City, NJ, USA, during October 23-26, 2011. The 37 revised full papers presented were carefully selected from 59 submissions. Conference papers are organized in 6 technical sessions, covering the topics of steganography and steganalysis, watermarking, visual cryptography, forensics, anti-forensics, fingerprinting, privacy and security.
Fast conference proceedings -- State-of-the-art report -- Up to date results.
Keywords: Computer science; Data structures (Computer science).; Data encryption (Computer science).; Information storage and retrieval systems; Computer graphics; Computer vision; Computer Science; Data Encryption; Data Structures, Cryptology and Information Theory; Data Encryption; Information Storage and Retrieval; Computer Graphics; Image Processing and Computer Vision